Microbial Community and in situ Bioremediation of Groundwater by Nitrate Removal in the Zone of a Radioactive Waste Surface Repository - Safonov, Alexey V.; Babich, Tamara L.; Sokolova, Diyana S.; Grouzdev, Denis S.; Tourova, Tatiyana P.; Poltaraus, Andrey B.; Zakharova, Elena V.; Merkel, Alexander Y.; Novikov, Alexander P.; Nazina, Tamara N. (Frontiers in Microbiology, 2018)
The goal of the present work was to investigate the physicochemical and radiochemical conditions and the composition of the microbial community in the groundwater of a suspended surface repository for radioactive waste (Russia) and to determine the possibility of in situ groundwater bioremediation by removal of nitrate ions. Groundwater in the repository area (10-m depth) had elevated concentrations of strontium, tritium, nitrate, sulfate, and bicarbonate ions. High-throughput sequencing of the V3-V4/V4 region of the 16S rRNA gene revealed the presence of members of the phyla Proteobacteria (genera Acidovorax, Simplicispira, Thermomonas, Thiobacillus, Pseudomonas, Brevundimonas, and uncultured Oxalobacteraceae), Firmicutes (genera Bacillus and Paenibacillus), and Actinobacteria (Candidatus Planktophila, Gaiella). Canonical correspondence analysis suggested that major contaminant – nitrate, uranium and sulfate shaped the composition of groundwater microbial community. Groundwater samples contained culturable aerobic organotrophic, as well as anaerobic fermenting, iron-reducing, and denitrifying bacteria. Pure cultures of 33 bacterial strains belonging to 15 genera were isolated. Members of the genera Pseudomonas, Rhizobium, Cupriavidus, Shewanella, Ensifer, and Thermomonas reduced nitrate to nitrite and/or dinitrogen. Application of specific primers revealed the nirS and nirK genes encoding nitrite reductases in bacteria of the genera Pseudomonas, Rhizobium, and Ensifer. Nitrate reduction by pure bacterial cultures resulted in decreased ambient Eh. Among the organic substrates tested, sodium acetate and milk whey were the best for stimulation of denitrification by the microcosms with groundwater microorganisms. Injection of these substrates into the subterranean horizon (single-well push-pull test) resulted in temporary removal of nitrate ions in the area of the suspended radioactive waste repository and confirmed the possibility for in situ application of this method for bioremediation.